2007
DOI: 10.1038/sj.gt.3302912
|View full text |Cite
|
Sign up to set email alerts
|

Gene transfer of SHIP-1 inhibits proliferation of juvenile myelomonocytic leukemia cells carrying KRAS2 or PTPN11 mutations

Abstract: Juvenile myelomonocytic leukemia (JMML) is a malignant disease of early childhood characterized by a hypersensitivity to granulocyte/macrophage colony-stimulating factor (GM-CSF). Mutations in RAS or PTPN11 are frequently detected in JMML patients. The SH2-containing inositol 5-phosphatase 1 (SHIP-1) is a negative regulator of GM-CSF signaling, and inactivation of SHIP-1 in mice results in a myeloproliferative disease. Here, we report the effects of SHIP-1 expression on GM-CSF-dependent proliferation and colon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 19 publications
0
12
0
Order By: Relevance
“…SHIP-1-deficient mice develop a myeloproliferative disease [138] and an inactivating point mutation ( SHIP V684E ) has been observed in approximately one of thirty AML cases [137]. Also another mutation, SHIP Q1154L , has been observed in AML, but was even less frequent (1 of 192 cases) [138].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…SHIP-1-deficient mice develop a myeloproliferative disease [138] and an inactivating point mutation ( SHIP V684E ) has been observed in approximately one of thirty AML cases [137]. Also another mutation, SHIP Q1154L , has been observed in AML, but was even less frequent (1 of 192 cases) [138].…”
Section: Introductionmentioning
confidence: 99%
“…SHIP-1-deficient mice develop a myeloproliferative disease [138] and an inactivating point mutation ( SHIP V684E ) has been observed in approximately one of thirty AML cases [137]. Also another mutation, SHIP Q1154L , has been observed in AML, but was even less frequent (1 of 192 cases) [138]. Though some studies confirmed, that SHIP-1 is a leukemia suppressor [137, 138] it is unlikely that SHIP1 mutations are a frequent cause of Akt-activation in AML.…”
Section: Introductionmentioning
confidence: 99%
“…Human SHIP1 cDNA and an enzymatic inactive SHIP1 mutant (D672A) 5,6 were cloned in the lentiviral vector pRRL.PPT.CMV.GFPpre. 293T cells were cultured in Dulbecco's modified Eagle's medium supplemented with 10% fetal calf serum and 2 mM glutamine.…”
Section: Lentiviral Vectorsmentioning
confidence: 99%
“…5 Gene transfer of INPP5D in CD34 + cells from patients with juvenile myeloid leukemia carrying mutations in KRAS2 or PTPN11 reduced their hypersensitivity for granulocyte macrophage-colony stimulating factor (GM-CSF). 6 In this report, we characterized the inhibitory effects of SHIP1 on the GM-CSF-dependent and autonomous proliferation of CD34 + cells from AML patients.…”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12] Furthermore, we have demonstrated that overexpression of SHIP1 in primary leukemia cells from patients suffering from juvenile myelomonocytic leukemia or AML reduces the proliferation of the leukemia cells in vitro. 13,14 In addition, it has been shown that accompanying deletion of PTEN and SHIP1 causes development of lethal B cell lymphomas in mice. 15 These data strongly point to a tumor suppressor function of SHIP1 in haematopoietic cells.…”
Section: Introductionmentioning
confidence: 99%